Ambient Air Quality and Respiratory Problems in Turkey - Kavakli, Mustafa; Goksel Ozdilek, Hasan (Asian Journal of Chemistry, 2010)
Rapid development in Turkey, especially over the last 25 years, has provided better living standards for its residents, yet the quality of the environment has not been taken into account seriously. Air pollution monitoring in many centres has been into operation since early 1990's in Turkey. 50 Province center are known to have impaired outdoor air quality in the country. On the contrary, some cities have transformed their residential heating system by relying on imported natural gas, while some others have relatively better air due to their year-round warmer temperatures. In this study, the number of cases of upper respiratory sickness, sinusitis, bronchitis, tonsillitis, laryngitis and pharyngitis, together with various some factors, namely outdoor air sulphur dioxide, vehicle density, wind rate and mean ambient air temperature and population density were investigated by multi regression to establish whether they were linked or not. It was determined that population density is the most important factor in the cases of the examined health problems.